Learning and the reproduction of societies: Four theses on the efficacy of ideology in schools - Brandmayr, Michael (Momentum Quarterly, 2017)
The paper discusses, under which preconditions certain practices in schools can be described as ideologies and in which forms schools participate on the reproduction and distribution of ideologies in society. It elaborates four assumptions on the effectiveness of ideologies in schools, regarding the problems of an economic functionalism in modes of learning, the question of the social in processes of subjectivation and the dialectics in the distribution process of ideology. These assumptions are based on a discourse analysis that examined the guiding conceptions of ideal learning in the Austrian educational system currently in use (Brandmayr 2017). The findings of this analyzes are presented after a discussion of the term ideology. Ideology is therby understood as being distributed by practices, in schools this means mainly by learning processes. Those practices structure modes of perception and interpretation and guide processes of subjectivation. So by analyzing learning practices in schools, it can be questioned, how do schools contribute to the ideological distribution and therefore also to the reproduction of societies.
Keywords: discourse on school development; learning; ideology; reproduction; subjectivation